Pengaruh Pengendalian Internal, Whistleblowing System, dan Komitmen Organisasi Terhadap Pencegahan Fraud - Andani Rizki Putri; Munari Munari (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the influence of internal control, whistleblowing system, and organizational commitment on fraud prevention in village fund management. The emergence of irregularities in village fund administration indicates weak oversight mechanisms and a lack of ethical awareness among village officials in adhering to public accountability standards. This research was conducted using a quantitative survey approach through the distribution of questionnaires to 84 village officials from 12 villages in Lamongan District, Lamongan Regency. The collected data were processed using multiple linear regression analysis with SPSS version 30. The results show that internal control has a positive and significant effect on fraud prevention with a significance value of 0.039. The whistleblowing system also has a positive and significant effect with a significance value of 0.001, and organizational commitment likewise shows a positive and significant effect with a significance value of 0.001. Simultaneously, the three variables significantly influence fraud prevention, as indicated by an F-value of 87.410, which is greater than the F-table value of 3.1108. The Adjusted R Square value of 0.757 indicates that internal control, whistleblowing system, and organizational commitment explain 75.7% of the variation in fraud prevention. These findings emphasize the importance of strengthening village governance by implementing effective internal control systems, providing secure and reliable whistleblowing mechanisms, and building an organizational culture grounded in honesty, integrity, and moral responsibility to achieve transparent and fraud-free village fund management.